2022
DOI: 10.1186/s12877-022-03493-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between physical activity trajectories and frailty: a 20-year prospective cohort among community-dwelling older people

Abstract: Background Studies on examining the relationship between physical activity patterns and frailty are lacking. This study examined physical activity patterns in older people and investigated the relationship between physical activity and frailty as well as identifying the predictors of frailty. Methods We used a nationally representative longitudinal database, the Taiwan Longitudinal Study of Aging (TLSA) database, and data for a 20-year period were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
2
1
0
Order By: Relevance
“…Our ndings showed that sedentary activity level was associated with frailty in older adults. This ndings in agreement with the results of previous studies conducted among older adults in Taiwan and Brazil [28,29]. A study from Taiwan found four trajectories of physical activity among older adults: consistently physically inactive, consistently physically active, incline, and decline in physical activity [29].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our ndings showed that sedentary activity level was associated with frailty in older adults. This ndings in agreement with the results of previous studies conducted among older adults in Taiwan and Brazil [28,29]. A study from Taiwan found four trajectories of physical activity among older adults: consistently physically inactive, consistently physically active, incline, and decline in physical activity [29].…”
Section: Discussionsupporting
confidence: 92%
“…This ndings in agreement with the results of previous studies conducted among older adults in Taiwan and Brazil [28,29]. A study from Taiwan found four trajectories of physical activity among older adults: consistently physically inactive, consistently physically active, incline, and decline in physical activity [29]. The decline in physical activity group had the highest frailty score, while the incline group had the lowest frailty score, after 20 years of follow-up [29].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation